Omecamtiv mecarbil in chronic heart failure with reduced ejection fraction: GALACTIC‐HF baseline characteristics and comparison with contemporary clinical trials. (27th October 2020) - Teerlink, John R.; Diaz, Rafael; Felker, G. Michael; McMurray, John J.V.; Metra, Marco; Solomon, Scott D.; Adams, Kirkwood F.; Anand, Inder; Arias‐Mendoza, Alexandra; Biering‐Sørensen, Tor; Böhm, Michael; Bonderman, Diana; et al.
Abstract : Aims: The safety and efficacy of the novel selective cardiac myosin activator, omecamtiv mecarbil, in patients with heart failure with reduced ejection fraction (HFrEF) is being tested in the Global Approach to Lowering Adverse Cardiac outcomes Through Improving Contractility in Heart Failure (GALACTIC‐HF) trial. Here we describe the baseline characteristics of participants in GALACTIC‐HF and how these compare with other contemporary trials. Methods and results: Adults with established HFrEF, New York Heart Association (NYHA) functional class ≥II, ejection fraction ≤35%, elevated natriuretic peptides and either current hospitalization for heart failure or history of hospitalization/emergency department visit for heart failure within a year were randomized to either placebo or omecamtiv mecarbil (pharmacokinetic‐guided dosing: 25, 37.5, or 50 mg bid). A total of 8256 patients [male (79%), non‐white (22%), mean age 65 years] were enrolled with a mean ejection fraction 27%, ischaemic aetiology in 54%, NYHA class II 53% and III/IV 47%, and median N‐terminal pro‐B‐type natriuretic peptide 1971 pg/mL. Heart failure therapies at baseline were among the most effectively employed in contemporary heart failure trials. GALACTIC‐HF randomized patients representative of recent heart failure registries and trials with substantial numbers of patients also having characteristics understudied in previous trials including more from North America ( n  = 1386), enrolled as inpatients ( n  = 2084), systolic blood pressure <100 mmHg ( n  = 1127), estimated glomerular filtration rate <30 mL/min/1.73 m 2 ( n  = 528), and treated with sacubitril/valsartan at baseline ( n  = 1594). Conclusions: GALACTIC‐HF enrolled a well‐treated, high‐risk population from both inpatient and outpatient settings, which will provide a definitive evaluation of the efficacy and safety of this novel therapy, as well as informing its potential future implementation. Abstract : Graphical representation of the GALACTIC‐HF trial design, enrolment and baseline characteristics. ACEi, angiotensin‐converting enzyme inhibitor; ARB, angiotensin receptor blocker; ARNi, angiotensin receptor–neprilysin inhibitor; CRT, cardiac resynchronization therapy (biventricular pacemaker); CV, cardiovascular; EF, ejection fraction; HFrEF, heart failure with reduced ejection fraction; ICD, implantable cardioverter defibrillator; NT‐proBNP, N‐terminal pro‐B‐type natriuretic peptide; NYHA, Hew York Heart Association; SBP, systolic blood pressure.